Self-Employment in the Light of Pursuit of Activities in Other Member States - Szypniewski, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The purpose of the following study is to analyze the forms of temporary activity in the territory of another Member State. First, the author analyzes the assumptions of the law on the temporary performance of activities in another country (“self-posting”). In addition to that, the author discusses the assumptions of the right to pursue an activity in two or more Member States. In the considerations, the author focuses on the dogmatic and legal analysis of the European Union regulations on the principles of coordination of social security systems, also recalling the case law of Polish courts.